A novel approach for anatomical repair of ventral hernia with modified smead jones technique - Chatterjee, Sudipta; Chakraborty, Shobhik; Meena, Shivani (International Journal of Research in Medical Sciences, 2024)
Background: Ventral hernia repair is the most popular procedures done worldwide. Despite of enough literature, evidence for optimal repair is lacking. We introduced a novel surgical technique for open primary ventral hernia repair, using modified smead jones technique. Methods: This prospective interventional study conducted at the department of general surgery in Midnapore Medical College and Hospital from October 2022 to February 2023 aimed to assess the efficacy of the modified smead jones technique in open primary ventral hernia repair. Results: Thirty cases were enrolled, predominantly featuring umbilical hernias in females aged 51-60 years. All cases presented with swelling, pain, and irreducibility. The Modified smead jones technique, employing Prolene no. 1, was utilized, with post-operative complications primarily comprising superficial wound infections managed by IV antibiotics and post-operative pain addressed with adequate analgesia. Recurrence was not observed during follow-ups at 15 days, 1 month, 6 months, and 12 months. Conclusions: The study concludes that this modified technique offers a straightforward approach with low rates of early and potential reduction in late complications, serving as a viable alternative in both elective and emergency settings for primary ventral hernia repair.